Investigations of stability and transition of a jet in crossflow using DNS - Peplinski, A.; Schlatter, Philipp; Henningson, D. S. (Kluwer Academic Publishers, 2015)
We study the stability of a jet in crossflow at low values of the jet-tocrossflow velocity ratio R focusing on direct numerical simulations (DNS) and the global linear stability analysis adopting a time-stepper method. For the simplified setup neglecting a meshed pipe in the simulations, we compare results of the fullyspectral code SIMSON with the spectral-element code Nek5000. We find the calculated critical value R for the first bifurcation to be dependent on the numerical method used. This result is related to a large sensitivity of the eigenvalues and to the large spatial growth of the corresponding eigenmodes, making the use of periodic domains, even with the fringe method, difficult. However, we observe a similar sensitivity to reflection from the outflow boundary in the inflow/outflow configuration as well.We apply in our studies both modal and non-modal analyses investigating transient effects and their asymptotic fate, and we find transient wavepacket that develop almost identically in the stable and unstable cases. Finally, we compare these results with the simulation including the pipe in the computational domain finding the latter one to be much more unstable.
CRIS-Team Scopus Importer:2023-03-21